2023
DOI: 10.1136/bmjopen-2022-069091
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to return to work following cardiovascular disease: a systematic review and meta-synthesis of qualitative research

Abstract: ObjectivesReturn to work is a key rehabilitation goal, however, people recovering from cardiovascular disease (CVD) often struggle with returning to work. The aim of this study was to conduct a systematic review and meta-synthesis of the existing qualitative evidence on barriers and facilitators to return to work experienced by people with CVD.MethodsA systematic literature search was conducted in PubMed, Embase, Web of Science, PsycINFO, Scopus and CINAHL in August 2022. The reference lists of the included ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(212 reference statements)
0
2
0
Order By: Relevance
“…This aligns with literature highlighting the importance of psychological aspects in chronic illness management. 22 Emotional balance and belief in fate seemed to have given the participants the strength to face their health challenges.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with literature highlighting the importance of psychological aspects in chronic illness management. 22 Emotional balance and belief in fate seemed to have given the participants the strength to face their health challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to RTW are part of a complex process that includes a lack of suitable social support, a lack of appropriate jobs, and a lack of up-to-date skills. 8 , 9 , 10 Greidanus et al. 10 found that cancer survivors reported RTW-related barriers that included support, communication, work environment, discrimination, and perception of work ability.…”
Section: Introductionmentioning
confidence: 99%